Effect of Instagram Promotion towards Buying Intention and Buying Decision of Pekopurin.id - Sutjiadi, Inez; Prasetya, Wibawa (LSPR Institute of Communication & Business, 2021)
Promotion through social media is very easy, fast and certainly not paid then many marketers take advantage of this opportunity to introduce new products. Social media that commonly used is Facebook, Instagram, Twitter, YouTube and other social media. Online shop owners should be able to introduce new products in a way that is unique and different from others. The objectives in this study are to analyze the effect of promotion on the influence of buying interest, and purchasing decision of Pekopurin.id product through Instagram. This research used S-O-R (Stimulus-Organism-Response) theory. In this study, promotion is a stimulus of interesting photographs followed by buying interest as a response. This research uses quantitative method with explanative approach causality. The study was conducted by distributing questionnaires to 145 respondents with simple random sampling technique. The conclusion from this research is the results show that promotion has an influence on purchasing decisions. This means there are other factors that can influence the purchase decision. So, it is necessary to do further research to complete the research that has been made. The advice from this research is Pekopurin.id is advised to post photos of the atmosphere during the event so that consumers can find out how the event situation ever followed by Pekopurin.id.